The Principal's Strategy in Implementing Computer Based Testing School Assessment at SMPIT Anak Sholeh Mataram - Muzanni, Muzanni; Sai, Muhammad; Khaldun, Rendra (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This case study research aims to examine and analyze the condition of information and communication technology facilities for implementing Computer Based Testing School Assessment exams, school principal strategies in implementing Computer Based Testing School Assessments, as well as obstacles in implementing School Assessments Computer Based Testing in one of the junior high schools in Mataram City, Nusa Tenggara Barat, Indonesia. Data was collected through interviews, observation and documentation. The results of data analysis show that the condition of computer facilities for implementing Computer-based National Exam in schools is inadequate. The principal's strategy in implementing the Computer Based Testing School Assessment includes strategies in the areas of facilities and infrastructure, human resources and student affairs. There are two obstacles in implementing the Computer Based Testing School Assessment that have emerged, namely technical and non-technical obstacles. This highlights the importance of the principal's strategy in ensuring the successful implementation of Computer Based Testing-Based School Assessment.